3(2y+1)+5(y-4)=-7
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 23:38:38
3(2y+1)+5(y-4)=-73(2y+1)+5(y-4)=-73(2y+1)+5(y-4)=-76y+3+5y-20=-76y+5y=-7+20-311y=10y=10÷11y=10/11
3(2y+1)+5(y-4)=-7
3(2y+1)+5(y-4)=-7
3(2y+1)+5(y-4)=-7
6y+3+5y-20=-7
6y+5y=-7+20-3
11y=10
y=10÷11
y=10/11
2(y-4)(3y+2)-5(-3y+7)(y+1),其中y=-1
4(2y+5)-3y=7(y-5)+4(2y+1)
4(5—2y)+7(y+1)=3(4y-1)+17求y
4*(5—2y)+7(y+1)=3(4y-1)+17求y
[T,Y]=ode45(@rigid,[0 1],[rand(15,1)]);plot(T,Y(:,1),'-',T,Y(:,2),'-.',T,Y(:,3),'.',T,Y(:,4),'-',T,Y(:,5),'-.',T,Y(:,6),'.',T,Y(:,7),'-',T,Y(:,8),'-.',T,Y(:,9),'.',T,Y(:,10),'-',T,Y(:,11),'-.',T,Y(:,12),'-.',T,Y(:,13),'.',T,Y(:,14),'-',T,Y(:,15),'.')
(y-4)(3y+2)-(3y-7)(2y+1),其中y=4/3
5(y-2)-7(y+3)=11(y+4)
(2y-3)(-y+4)=(y-2)(y-5)-3y(y-7/3)解方程
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
已知(3x+1)(3x-3)-3x+2)^2=-7,(y+7)(y-7)-y(y-7)=0,求8y^2-5y(-y+3x)+4y(-4y-5/2x)的值
y-1/y-2 - y-3/y-4=y-2/y-3 - y-4/y-5一共有四个分数哦~希望可以快一点~谢谢!
若 4y^2-2y+5=7 则 2y^2-y+1=?
3-5-2y/5=y-4-7y/10+y+2/2
3(2y+1)+5(y-4)=-7
10y-2(7y-2)=5(4y+5)-3y
10y+2(7y-2)=5(4y+3)+3y怎么算